Experimental study of fatigue life of wagon wheel of increased hardness when interacting with rail - M. I. Biserikan; S. V. Petrochenko; K. V. Averkov (Омский научный вестник)
The analysis of the processes occurring during the interaction of the wheel with the rail. Studies of the processes occurring in the interaction of the wheel with the rail by the method of similarity were carried out. The occurrence of contact fatigue surface defects is visually monitored. It is concluded that the maximum height of the waviness on the surface of the roller is related to the speed of damage to its surface. The dependence is constructed, which allows to determine the number of cycles of impact applied to the surface of the roller load, depending on the macrogeometric parameters of its surface. Conclusions about the acceleration of the development of contact fatigue defects with increasing macrogeometrical deviations are made.